No increased chromosome breakage in three Bloom's syndrome heterozygotes. - Kuhn, E M (1979)
The frequency of chromosome aberrations in the lymphocytes of three established heterozygotes for the Bloom's syndrome gene (ages 67, 57, 46) was compared to that in controls (ages 68, 67, 61, 46, 34). The main part of the study was done on coded slides. No difference was found between the heterozygotes and the control group, except for one control (aged 46) who had a significantly higher number of chromosome aberrations than the others.